2008
DOI: 10.1177/0363546508324970
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Treatment for Osteochondritis Dissecans of the Capitellum

Abstract: Spontaneous healing potential of osteochondritis dissecans in early lesions, especially in patients with open capitellar growth plates, appears high, and nonoperative treatment is appropriate. Conversely, healing potential is extremely low in advanced osteochondritis dissecans lesions. Surgical intervention is recommended to achieve lesion healing in advanced cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
133
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 23 publications
1
133
0
1
Order By: Relevance
“…Stable lesions can be managed successfully with non-operative measures including rest and activity modification. Factors associated with a good prognosis include early lesions, patients with open capitellar growth plates [26], and localized subchondral bone flattening without fragmentation [27,28]. However, healing with non-operative management becomes very unlikely in those with closed growth plates and lesion instability even without displacement [26,28,27,29].…”
Section: Classificationmentioning
confidence: 99%
“…Stable lesions can be managed successfully with non-operative measures including rest and activity modification. Factors associated with a good prognosis include early lesions, patients with open capitellar growth plates [26], and localized subchondral bone flattening without fragmentation [27,28]. However, healing with non-operative management becomes very unlikely in those with closed growth plates and lesion instability even without displacement [26,28,27,29].…”
Section: Classificationmentioning
confidence: 99%
“…This involves immediate cessation of aggravating activities that load the radiocapitellar joint, i.e., throwing, gymnastics, weightlifting [6,7,19,40,41]. Some authors advocate the use of a hinged elbow brace for a period of 1-6 weeks in the initial resting period to allow intermittent range of motion exercises to prevent stiffness, while others recommend rest without immobilization [6,19].…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…After an initial period of rest, physical therapy is initiated avoiding strengthening until resolution of symptoms [19]. Most athletes who respond to conservative management may start gentle overhead throwing at 3-4 months with return to play at 6 months [6,7,19,41].…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…38 Similarly, only 50% of patients treated nonoperatively with a closed physis in the series of Mihara et al demonstrated healing. 25 Aside from unstable lesions, surgical management is usually reserved for patients who fail 6 months of nonoperative management. Various surgical treatments have been proposed, including drilling, microfracture surgery, debridement, fragment excision, loose body removal, and OAT.…”
Section: Classificationmentioning
confidence: 99%